2015
DOI: 10.1002/jms.3584
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of sexual assault evidence: statistical classification of condoms by ambient mass spectrometry

Abstract: Desorption electrospray ionization mass spectrometry (DESI-MS) and easy ambient sonic-spray ionization mass spectrometry (EASI-MS) are employed here in the forensic analysis of chemical compounds found in condoms and relative traces, and their analytical performances are compared. Statistical analysis of data obtained from mass spectra only was applied in order to obtain classification rules for distinguishing ten types of condoms. In particular, two supervised chemometric techniques [linear discriminant analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…All of these are chemicals known to be found in condoms. [27] The Pasante warming and Amor lemon-flavoured condoms produced similar mass spectra.…”
Section: Condom Analysismentioning
confidence: 93%
See 1 more Smart Citation
“…All of these are chemicals known to be found in condoms. [27] The Pasante warming and Amor lemon-flavoured condoms produced similar mass spectra.…”
Section: Condom Analysismentioning
confidence: 93%
“…[23][24] Furthermore, van Helmond et al demonstrated the classification of condom lubricants in treated fingerprints using DESI-MS. [25] Furthermore, chemometric strategies have been developed capable of differentiating between condom brands based on their chemical profiles. [26], [27] In light of this, it is therefore important to demonstrate that any techniques developed for the direct analysis of suspected semen, would also be capable of detecting components pertinent to condoms and lubricants, in order to develop a technique more widely applicable to sexual assault evidence analysis.…”
Section: Condom Analysismentioning
confidence: 99%
“…The compounds commonly used in lubricated condoms formulations such as polymers (nonoxynol-9, polyethylene glycol, polydimethylsiloxane) and small molecules additives (N-methylmorpholine, N-octylamine, N,N-dibutyl formamide, isonox 132) were successfully determined by DESI-MS [27]. Moreover, a successful statistical classification of ten types of condoms by DESI-MS with 94% prediction ability was presented [30]. When handling, chemical components of condoms might be transferred and deposited with the fingerprint.…”
Section: Applicationmentioning
confidence: 99%
“…Spectroscopic methods, however, lack the selectivity to identify low‐abundance species in the presence of large excesses of PDMS or PEG, and the power of chromatography‐based analyses is negated by the time‐consuming nature of the methodology. To circumvent these limitations while maintaining the sensitivity and selectivity afforded by mass spectrometry, direct sampling ion sources have been successfully deployed for lubricant analysis, including matrix‐assisted laser desorption/ionisation (MALDI), desorption electrospray ionisation (DESI) and easy ambient sonic‐spray ionisation (EASI) . MALDI is ideally suited to the analysis of polymeric components in lubricants, but is susceptible to interference from matrix ions with mass‐to‐charge ratios ( m/z ) less than 400, potentially obscuring analysis of low‐mass components present at trace levels.…”
Section: Introductionmentioning
confidence: 99%